Experimental investigation on thermal insulation performance of air interlayer under an impinging jet at high temperature. Issue 3 (September 2019) - Cai, Jian; Ye, Wei; Zhi, Chengqiang; Huang, Yixiang; Zhang, Xu
Abstract: Air interlayers are widely used in building envelope to reduce heat transfer between indoor and outdoor environments. However, it is less common to apply to industrial processes in confined spaces, especially when the heating source is at high temperature with high velocity. In this paper, a special structure with air interlayer between two plates for thermal insulation was derived from an industrial manufacturing application. The effects of the interlayer on heat transfer was investigated under an impinging jet at high temperature. An experimental mock-up was designed to produce high temperature (∼ 500 °C) impinging gas jet with relative stable high velocity (∼56 m/s) at the nozzle exit. The impingement surface of the test structure was covered with a 2mm thick stainless-steel plate at a distance of 5mm, which formed a horizontal air insulation layer. Benchmark test was also conducted after the removal of the stainless-steel layer. In each case, a standard procedure within a duration of 30 min was applied to minimize the variations of testing conditions. The temperatures at both inner and outer surfaces of the structure, as well as the temperatures from inside and outside the air interlayer, were measured by thermocouples. In addition, an analytical model to account for the effects of air insulation was proposed to compared with experiments. The results showed that, the air interlayer can reduce the highest temperatures for about 48 °C. The temperature difference at the end of the experiment was about 30 °C. The analytical model was in good agreement with the experimental data and the maximum difference was ∼6.5 °C.